Unlocking high-performance near-infrared photodetection: polaron-assisted organic integer charge transfer hybrids - Muhammad Ahsan Iqbal; Xueqian Fang; Yasir Abbas; Xiaoliang Weng; Tingchao He; Yu-Jia Zeng (Light: Science & Applications)
Abstract Room temperature femtowatt sensitivity remains a sought-after attribute, even among commercial inorganic infrared (IR) photodetectors (PDs). While organic IR PDs are poised to emerge as a pivotal sensor technology in the forthcoming Fourth-Generation Industrial Era, their performance lags behind that of their inorganic counterparts. This discrepancy primarily stems from poor external quantum efficiencies (EQE), driven by inadequate exciton dissociation (high exciton binding energy) within organic IR materials, exacerbated by pronounced non-radiative recombination at narrow bandgaps. Here, we unveil a high-performance organic Near-IR (NIR) PD via integer charge transfer between Poly[2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene] (C-14PBTTT) donor (D) and Tetrafluorotetracyanoquinodimethane (TCNQF4) acceptor (A) molecules, showcasing strong low-energy subgap absorptions up to 2.5 µm. We observe that specifically, polaron excitation in these radical and neutral D-A blended molecules enables bound charges to exceed the Coulombic attraction to their counterions, leading to an elevated EQE (polaron absorption region) compared to Frenkel excitons. As a result, our devices achieve a high EQE of ∼107%, femtowatt sensitivity (NEP) of ~0.12 fW Hz-1/2 along a response time of ~81 ms, at room temperature for a wavelength of 1.0 µm. Our innovative utilization of polarons highlights their potential as alternatives to Frenkel excitons in high-performance organic IR PDs.